Application of the electron backscateered diffraction method in microstructure research for determining of causes of metal structures destruction - L. V. Markova; V. V. Koleda; N. S. Kolodinskaya (Приборы и методы измерений)
The application of the diffraction method for backscattered electrons allows us to take a fresh look at the structural changes in the material as a whole and on the processes of destruction of metal structures in particular. The aim of this work was to apply the method of diffraction of backscattered electrons to reveal the characteristic distinctive features of the structure of the material in areas under the fracture and away from it.The diffraction of backscattered electrons is a method that allows one to determine the orientation of individual grains, the local texture, and also to identify the phases in the sample under research. This method can determine local and general deformations, the number of recrystallized and deformed grains, the size and misorientation of grains, etc.The results of a study of the mast fragment of the unit for drilling and repairing wells with a carrying capacity of 200 tons (APC-200) are presented with the establishment of characteristic structural differences between the sites under the fracture and away from it.The appearance and development of a subgrain structure at the site under the slope is established. It is shown that the material of the mast was made of rolled metal, for which no additional heat treatment was carried out, and destruction could occur at almost any point.